Effect of High-Volume Hemofiltration in Critically Ill Patients: A Systematic Review and Meta-Analysis - Junhai, Zhen (Med Sci Monit, 2019)
BACKGROUND: Studies have been carried out to assess the efficacy of high-volume hemofiltration (HVHF) among critically ill patients. However, it is currently unclear whether HVHF is really valuable in critically ill patients. MATERIAL/METHODS: Randomized controlled trials evaluating HVHF for critically ill adult patients were included in this analysis. Three databases were searched up to July 27, 2018. The relative risk (RR), mean difference (MD), and 95% confidence intervals (CI) were determined. RESULTS: Twenty-one randomized controlled trials were included in this analysis. Overall, HVHF was associated with lower mortality compared with control measures (RR=0.88, 95% CI=0.81 to 0.96, P=0.004) in critically ill patients. Sub-analysis revealed HVHF reduced mortality in sepsis and acute respiratory distress syndrome patients, but no similar effect in other diseases. HVHF decreased levels of plasma tumor necrosis factor and interleukin 6. The heart rate of the HVHF group after treatment was slower than the control group, while we found higher mean arterial pressure in the HVHF group, but oxygenation index was not significantly different between the two groups. HVHF had no remarkable influence on acute physiological and chronic health evaluation score (APACHE II score) compared with the control group. CONCLUSIONS: HVHF might be superior to conventional therapy in critically ill patients.